Hydrogel-mediated local delivery of dexamethasone reduces neuroinflammation after traumatic brain injury. (26th February 2021) - Jeong, Da Un; Bae, Sooneon; Macks, Christian; Whitaker, Joseph; Lynn, Michael; Webb, Ken; Lee, Jeoung Soo
Abstract: Excessive and prolonged neuroinflammation leads to neuronal cell death and limits functional recovery after traumatic brain injury (TBI). Dexamethasone (DX) is a steroidal anti-inflammatory agent that is known to attenuate early expression of pro-inflammatory cytokines associated with activated microglia/macrophages. In this study, we investigated the effect of dexamethasone-conjugated hyaluronic acid (HA-DXM) incorporated in a hydrolytically degradable, photo-cross-linkable poly (ethylene) glycol-bis-(acryloyloxy acetate) (PEG-bis-AA) hydrogel on the inflammatory response, apoptosis, and functional recovery in a controlled cortical impact (CCI) rat TBI model. In vitro, DX release from PEG-bis-AA/HA-DXM hydrogel was slow in phosphate-buffered saline without enzymes, but significantly increased in the presence of hyauronidase/esterase enzymes. TBI was generated by a CCI device armed with a 3 mm tip (3.5 m s −1, depth: 2 mm) and treated immediately with PEG-bis-AA/HA-DXM hydrogel. PEG-bis-AA/HA hydrogel without DX was used for comparison and untreated TBI group was used as a control. Significant reductions in cavity size, inflammatory response, and apoptosis were observed in animals treated with PEG-bis-AA/HA-DXM compared to those receiving PEG-bis-AA/HA and untreated. Animals receiving the PEG-bis-AA/HA-DXM hydrogel also exhibited higher neuronal cell survival and improved motor functional recovery compared to the other two groups.